Transport industry as factor of specialization of legal work - Гусарєва, Олена Станіславівна; Олексієнко, Сергій Борисович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
Тhe article examines the characteristics of common features and specific definition of professional legal experiencein the field of transport.